A neuro‐based approach to designing a Wilkinson power divider. Issue 3 (26th December 2019) - Jamshidi, Mohammad (Behdad); Lalbakhsh, Ali; Lotfi, Saeedeh; Siahkamari, Hesam; Mohamadzade, Bahare; Jalilian, Jaafar
Abstract: In this paper, a new neuro‐based approach using a feed‐forward neural network is presented to design a Wilkinson power divider. The proposed power divider is composed of symmetrical modified T‐shaped resonators, which are a replacement for quarter‐wave transmission lines in the conventional structure. The proposed technique reduces the size of the power divider by 45% and suppresses unwanted bands up to the fifth harmonics. To verify the concept, a prototype of the power divider has been fabricated and tested, exhibiting good agreement between the predicted and measured results. The results show that the insertion loss and the isolation at the center frequency are about 3.3 ± 0.1 dB and 23 dB, respectively.